PENGARUH PERCEIVED SECURITY, PERCEIVED RISK, PERCEIVED USEFULNESS, DAN PERCEIVED EASE OF USE TERHADAP MINAT PENGGUNAAN DOMPET - Anam, Khoirul; Rakhmawati, Antin (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract : This study aims to analyze the influence of Perceived Security, Perceived Risk, Perceived Usefulness, and Perceived Ease of Use on the intention to use digital wallets among Small and Medium Enterprises (SMEs) in Pasuruan Regency. The research employed a quantitative method with an explanatory research approach. Data were collected through questionnaires distributed to 136 SME respondents and analyzed using statistical techniques to examine causal relationships between variables. The findings reveal that all four independent variables, both partially and simultaneously, have a positive and significant effect on the intention to use digital wallets. These results indicate that higher perceived security, lower perceived risk, greater perceived usefulness, and better ease of use significantly increase SMEs’ intention to adopt digital wallets as a transaction tool. This study contributes to the development of a more contextual Technology Acceptance Model (TAM) in the SME sector and provides recommendations for service providers, local governments, and financial authorities to enhance literacy, security, and trust in digital wallet services.Keywords: Perceived Security, Perceived Risk, Perceived Usefulness, Perceived Ease of Use, Digital Wallet, SMEs.